The reason to sing - Carnelia, Craig (Routledge, Taylor & Francis Group, 2021)
"In The Reason to Sing, renowned composer-lyricist and teacher Craig Carnelia provides musical actors a step-by-step guide to making their singing performances more truthful, vivid, and full of life. Using a technique developed over decades of teaching the professional community of Broadway actors and students alike, The Reason to Sing utilizes detailed descriptions of sessions the author has had with his notable students and lays out a new and proven approach to help you build your skills, your confidence and your career. This book is intended for musical theater acting students as well as working professionals and teachers of the craft"--